In-hospital mortality among hospitalized COVID-19 patients in a tertiary care hospital in Dhaka City: a retrospective cohort study - Hossain, Ahmed; Hasan, Md. Maruf; Kamal, S. M. Sorowar; Dewan, Shahnewaz; Ahsan, Gias U.; Rana, Juwel (Frontiers in Medicine, 2025)
BackgroundIn-hospital mortality during COVID-19 treatment is a crucial metric used to assess the severity of the disease and the effectiveness of medical interventions. By identifying mortality risk factors, we aim to inform policy decisions, optimize resource allocation, and improve preparedness for future pandemics.MethodsThis retrospective cohort study was conducted at a tertiary hospital in Dhaka City, Bangladesh. Data were gathered from the hospital’s electronic medical records between July 2021 and September 2021. After applying specific inclusion and exclusion criteria, 218 patients with complete medical records were selected for the analysis. The independent variables examined included demographic characteristics, comorbidities, and clinical features. To assess in-hospital mortality, relative risks (RR) and 95% confidence intervals were calculated using multivariable logistic regression analysis employing the Delta method.ResultsThe study included 218 hospitalized COVID-19 patients, primarily male (51.4%) with an average age of 56.4 years (standard deviation of 15 years). The overall in-hospital mortality rate was 18.3%. Older age (≥60) (RR:3.10, 95% CI: 1.16–8.29), long-standing hypertension (≥5 years) (RR:2.78, 95% CI:1.54–5.02), and chronic kidney disease (CKD) (RR:4.43, 95% CI:2.93–6.70) were significant risk factors for mortality. Patients with diabetes (≥3 years) had a moderately increased risk (RR:1.68, 95% CI: 1.01–2.83). Notably, shorter hospital stays (≤7 days) were associated with higher mortality, potentially due to delayed treatment initiation. Moreover, Vaccinated patients have a significantly lower risk of death (RR: 0.07) compared to unvaccinated patients, highlighting the protective effect of vaccination. Greater lung involvement (especially in lower lobes) and higher Total Severity Scores (TSS ≥ 14) strongly predict COVID-19 mortality, with non-survivors exhibiting significantly worse radiographic damage.ConclusionAge, particularly when combined with chronic conditions like hypertension or chronic kidney disease, is a key predictor of in-hospital COVID-19 mortality. While gender is not an independent risk factor, males tend to have higher mortality rates. Delayed treatment, reflected by shorter hospital stays, also increases risk. Vaccination markedly lowers mortality. In resource-limited settings, lower lobe involvement >50% and TSS ≥ 14 can serve as early triage markers to guide ICU admission or intensified care. These indicators should inform risk assessment tools, resource allocation, and targeted interventions to reduce pandemic-related mortality.